2015
DOI: 10.1055/s-0034-1395522
|View full text |Cite
|
Sign up to set email alerts
|

Ätiologie und Therapie der traumatischen Trommelfellperforation

Abstract: This is the first study about the aetiology of traumatic tympanic membrane perforations in Germany. There is no statistic difference between the 2 materials for tympanic membrane splinting. A traumatic tympanic membrane perforation should be treatet at least to improve the air conduction threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
2
0
4
Order By: Relevance
“…This is consistent with the analysis by Wahid FI et al Performed in Pakistan, which included 114 male-dominated patients (71%) with a sex ratio of 2.5 [2]. The mean age of the patients in our study was 28.6 years, close to the study done in Germany in 2015 by Kraus et al on traumatic tympanic perforations, which had an average age of 28.7 years [3]. These findings are also corroborated by another study conducted by Qureshi et al, who found that the average age was less than 30 years old [4].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the analysis by Wahid FI et al Performed in Pakistan, which included 114 male-dominated patients (71%) with a sex ratio of 2.5 [2]. The mean age of the patients in our study was 28.6 years, close to the study done in Germany in 2015 by Kraus et al on traumatic tympanic perforations, which had an average age of 28.7 years [3]. These findings are also corroborated by another study conducted by Qureshi et al, who found that the average age was less than 30 years old [4].…”
Section: Discussionsupporting
confidence: 92%
“…A large series by Lou et al reported that, in a Chinese population, the overwhelming cause of traumatic TMP was slap injuries (78.4%), while instrumentation was responsible for only 5.0% of injuries. A recent study from Germany demonstrated that an open-handed slap led to 37.4% of injuries, while cotton-tipped applicators represented 19.3% and barotrauma from high diving represented 13.0% of injuries . A study from Nigeria demonstrated that the most common causes of traumatic TMP were slaps to the head (35.9%) and road traffic injuries (23.5%) .…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective cohort studies describing the prevalence of different causes for traumatic TMPs have been reported, but a large national study regarding this issue is lacking . The present study used a national database to comprehensively analyze the mechanisms of injury for traumatic TMPs among patients presenting to the ED in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…kleinerer schlitzförmiger Perforationen mittels Silikonfolie und die Reposition und Aufrichtung der Perforationsränder gilt [8,28], wird international die Beobachtung des Spontanverlaufs favorisiert. In Deutschland liegt bisher eine Studie aus dem Jahr 2014 vor, in der die Ätiologie und erapie eines größeren Patientenkollektivs mit Schwerpunkt auf der Differenzierung der Ätiologie beschrieben wurde [12]; die erapie erfolgte bei allen Patienten mittels Schienung (Papier oder Silikonfolie), und die erzielte Verschlussrate wurde beschrieben.…”
Section: Spontaner Heilungsverlauf Traumatischer Trommelfellperforati...unclassified
“…Bei der Ursache "Schlag auf das Ohr" zeigt sich jedoch -wie auch in anderen Studien bereits beschrieben -, dass das linke Ohr wesentlich häufiger betroffen ist. Die von Kraus genannte Tatsache, dass die meisten Menschen Rechtshänder sind und dadurch das linke Ohr des Opfers häufiger getroffen wird, erscheint als logische Erklärung zu dieser auch von uns ermittelten Seitenverteilung [12].…”
Section: Diskussionunclassified